GEOLOGY OF CIBEUREUM AND SURROUNDING AREAS, CIBEUREUM DISTRICT, KUNINGAN REGENCY, WEST JAVA PROVINCE - Ahmadjayadi, Tigfhar; Pratiwi, Santi Dwi; Iskandarsyah, Teuku Yan Waliana Muda (Bulletin of Scientific Contribution, 2023)
This study compiled a comprehensive geological map of Cibeureum and its surrounding areas in Cibeureum District, Kuningan Regency, West Java, using primary data and systematic geological methods, including field observations, data sampling, and laboratory analysis. Geographically, the area is located at 108o 42' 33.75"–108o 45' 16.8" East Longitude and 7o 02' 10.31"–7o 04' 52.20" South Latitude. The main purpose of this study is to identify the geological characteristics and phenomena that might have occurred in the past as well as in the future. In this study, geomorphological analysis was carried out, based on morphography, morphometry, and morphogenetic interpretations; stratigraphic analysis, based on interpretation of rock units, ages, and depositional environments; and analysis of geological structures, based on interpretation of DEM data and field observations. The results showed that the study area consists of very fine-coarse sandstones with carbonate and non-carbonate properties, claystone, and tuff. The geomorphological units are divided into four, namely Volcanic Stepping Hills, Structural Stepping Hills, Denudational Plains, and Denudational Slightly Steep Low Hills. Geological structures found in the field are folds, faults and joints. Based on the distribution of lithology, reconstruction of strike-dip patterns, and biostratigraphy analysis, the depositional of informal lithostratigraphy units in the study area began in the Middle Miocene and continued into the Quartenary, starts from Sandstone Units (Tmpbp) in N10 to N21, Claystone Unit (Tmpbl) in N12 to N21, Interbedded Claystone and Sandstone Unit (Tmpblbp) in N16 to N19, and continued with the deposition of Tuff Unit (Qt).